Biomechanical study of different internal fixation devices for femoral neck fractures: finite element analysis based on different reduction qualities - Zhu, Zhexi; Tang, Zhongjian; Lu, Yafei; Yang, Tao; Lu, Jizhe; Pang, Chenglong; Wang, Bin (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo compare and analyze the biomechanical advantages and disadvantages of four cannulated screws (4CCS) internal fixation device, biplanar double support screw (BDSF) internal fixation device, and dynamic hip screw (DHS) internal fixation device in anatomical reduction, positive reduction, and negative reduction of femoral neck fractures with a Pauwels angle of 50° using the finite element method.MethodsBased on the finite element method, a femoral neck fracture model with a Pauwels angle of 50° was established. Anatomical reduction, positive reduction, and negative reduction femoral neck fracture models were respectively constructed on this basis. Then, 4CCS, BDSF, and DHS internal fixation devices were implanted into the three types of femoral neck models, resulting in a total of 9 groups of finite element models. Each fracture group was tested under an axial load of 2100 N, and the displacement of the femur and internal fixation devices, as well as the distribution of Von Mises stress (VMS), were measured.ResultsIn the femoral neck fracture model with a 50° Pauwels angle, maximum femoral displacement in the BDSF group was 3.412 mm for anatomical reduction, 3.459 mm for positive reduction, and 3.962 mm for negative reduction—all smaller than those in the 4CCS and DHS groups. For femoral head stress, the 4CCS group showed higher stress (42.90 Mpa) than BDSF (38.21 Mpa) and DHS (35.91 Mpa) under anatomical reduction. However, under positive and negative reduction, BDSF (23.75 Mpa and 27.9 Mpa) outperformed 4CCS (50.40 Mpa and 34.6 Mpa) and DHS (44.92 Mpa and 44.6 Mpa). Negative reduction models had significantly greater overall stress than positive reduction models, with positive reduction showing better stability. Under anatomical reduction, BDSF’s internal fixation stress (222.3 Mpa) and displacement (3.611 mm) differed notably from DHS (322.2 Mpa, 3.009 mm) and 4CCS (276.0 Mpa, 3.346 mm). Under positive and negative reduction, BDSF (247.4 Mpa/3.370 mm and 292.1 Mpa/3.865 mm) performed better than 4CCS (250.4 Mpa/3.480 mm and 293.1 Mpa/3.897 mm). BDSF and 4CCS had significantly lower internal fixation stress than DHS under positive and negative reduction, while no significant difference in internal fixation displacement was found between BDSF and DHS under these conditions.ConclusionFor femoral neck fractures with a Pauwels angle of 50° under anatomical reduction, positive reduction, and negative reduction, the BDSF internal fixation device has better biomechanical performance than the 4CCS and DHS internal fixation devices. Except for anatomical reduction, positive reduction can achieve better biomechanical results. The BDSF internal fixation technique can be considered a reliable closed reduction internal fixation technique for treating femoral neck fractures with different anatomical reductions.